(untitled) (Journal of the College of Basic Education, 2023)
A monitoring system is proposed to detect fire in an important building. In this paper, fibber optics is used as a connection cables and temperature sensing. Star topology has been proposed to connect all rooms in the specified building. The temperature values have been taken from the important rooms by optical sensors and fed in back-propagation neural network in order to diagnose fire occurrence or not.